Development of a Realistic Mathematics Education (RME)-Based Learning Module on Trigonometry for Grade X Vocational High School (SMK) Students - Rana Anjani (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2026)
This study aims to develop a learning module based on the Realistic Mathematics Education (RME) approach for Grade X vocational high school (SMK) students, focusing on the topic of Trigonometry. The research employs a Research and Development (R&D) design, adopting the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The research subjects comprised 72 Grade X students from SMK Negeri 2 Depok, divided into an experimental class and a control class. The research instruments included expert validation sheets, practicality questionnaires administered to both teachers and students, and observation sheets assessing the implementation fidelity of the RME-based learning module. The findings indicate that the developed module achieved a "very valid" level of validity, as evaluated by content experts (average score: 114) and media experts (average score: 82). Furthermore, the module was deemed practical by teachers (average score: 80) and students (average score: 78.28). Its effectiveness in the instructional process was confirmed by a high implementation fidelity rate of 90%. Consequently, the RME-based learning module is validated as valid, practical, and effective for use in Trigonometry instruction for vocational high school students.